2013
DOI: 10.3389/fpsyg.2013.00715
|View full text |Cite
|
Sign up to set email alerts
|

A componential view of children's difficulties in learning fractions

Abstract: Fractions are well known to be difficult to learn. Various hypotheses have been proposed in order to explain those difficulties: fractions can denote different concepts; their understanding requires a conceptual reorganization with regard to natural numbers; and using fractions involves the articulation of conceptual knowledge with complex manipulation of procedures. In order to encompass the major aspects of knowledge about fractions, we propose to distinguish between conceptual and procedural knowledge. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 33 publications
(46 reference statements)
8
84
1
6
Order By: Relevance
“…Hiebert & LeFevre (1986) stressed that teachers should focus on conceptual and procedural mathematical skills especially when doing two-step problems or more. One recently study (Gabriel et al, 2013) showed primary school children mastered the part-whole and proportion categories, but struggled to see fractions as numbers, and noted that equivalent fractions are very difficult to understand. This leads to not understanding operational procedures for doing fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Hiebert & LeFevre (1986) stressed that teachers should focus on conceptual and procedural mathematical skills especially when doing two-step problems or more. One recently study (Gabriel et al, 2013) showed primary school children mastered the part-whole and proportion categories, but struggled to see fractions as numbers, and noted that equivalent fractions are very difficult to understand. This leads to not understanding operational procedures for doing fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The issue I wish to raise in this commentary is not with the conclusions of Gabriel et al (2013), but rather a general issue concerning the notion of conceptual and procedural tasks in mathematics. One of the difficulties is that a single task can reflect both types of knowledge.…”
mentioning
confidence: 95%
“…In their recent article, Gabriel et al (2013) propose that the difficulty experienced by Belgian children in learning fractions stems from the fundamental dichotomy of procedural and conceptual knowledge of fractions. Indeed, the authors are not alone in this conclusion, as the procedural/conceptual knowledge divide has been a focus in several recent studies in numerical cognition (Hallett et al, 2010; Hecht and Vagi, 2012).…”
mentioning
confidence: 99%
“…Fractions have been used for centuries and are manipulated in a great variety of everyday life situations and in mathematics. Thus why is it so hard for pupils to learn and represent fractions (Gabriel et al, 2013)? Various models have been proposed in order to explain those difficulties (Behr et al 1983;Mamede et al, 2005;Grégorie, 2008).…”
Section: Introductionmentioning
confidence: 99%